معلومات المعلمات حول الأمراض المعدية والإجراءات المتبعة لضبط انتشارها في رياض الأطفال في مدينة اللاذقية (Latakia University Journal -Medical Sciences Series, 2017)
الوقاية الفعالة للأمراض المعدية في الروضات لا تحمي فقط صحة الأطفال والكادر بل تضمن بيئة تعلُّم مناسبة لدعم التطور الصحي للأطفال. لذلك هدفت هذه الدراسة الوصفية إلى تقييم معلومات جميع معلمات رياض الأطفال في 20 روضة تم اختيارها بطريقة عشوائية عنقودية في مدينة اللاذقية و ذلك حول الأمراض المعدية و الإجراءات المتبعة لضبط انتشارها، في الفترة من 18/3/2015 و لغاية 10/5/2015. تم جمع البيانات باستخدام استبيان مطور من قبل الباحثة تحققت له دلالات صدق و ثبات مناسبة للدراسة, وقد أظهرت نتائج الدراسة أن مستوى معلومات المعلمات كان متوسطاً حول تحديد أنواع الأمراض المعدية, و كان جيد جداً فيما يتعلق بمعلوماتهن حول طرق انتقال الأمراض المعدية والعوامل البيئية التي تسببها. و أوصت الدراسة بأن تقوم إدارة الروضة بالتعاون مع القطاعات الصحية ومديرية التربية والتعليم بإعداد وتصميم برامج للتثقيف الصحي حول ضبط الأمراض المعدية والوقاية من انتشارها في الروضات طوال فترة العام الدراسي, وتحديد استراتيجيات فعالة للتثقيف الصحي.Effective prevention of communicable diseases in kindergartens do not only protect the health of children and staff, but ensure learning heavenly environment to support the healthy development of children. So this descriptive study aimed to assess the information of all kindergartens Teachers in 20 kindergartens using a random sample of cluster method at Lattakia City about communicable diseases and procedures to adjust the spread from 18/3/2015 through 10/5/2015. Data was collected by using a questionnaire developed by the researcher has achieved validity and reliability suitable for the study. Results of the study showed that the level of information level was average about the types of infectious diseases and very good with regard to ways transmission of infectious diseases and environmental factors cause. The study recommended: that the kindergartens administration in collaboration with the health sectors and the Directorate of Education to prepare and plan for health education programs on adjusting and prevent infectious diseases from spreading in kindergartens throughout the study year period and to identify effective strategies for health education.